Estimating Adherence Based on Prescription or Dispensation Information: Impact on Thresholds and Outcomes. A Real-World Study With Atrial Fibrillation Patients Treated With Oral Anticoagulants in Spain - Hurtado-Navarro, Isabel; García-Sempere, Aníbal; Rodríguez-Bernal, Clara; Santa-Ana-Tellez, Yared; Peiró, Salvador; Sanfélix-Gimeno, Gabriel (Frontiers in Pharmacology, 2018)
Objective To estimate drug exposure, Proportion of Days Covered (PDC) and percentage of patients with PDC≥80% from a cohort of atrial fibrillation patients initiating oral anticoagulant (OAC) treatment. We employed three different approaches to estimate PDC, using either data from prescription and dispensing (PD cohort) or two common designs based on dispensing information only, requiring at least one (D1) or two (D2) refills for inclusion in the cohorts. Finally, we assessed the impact of adherence on health outcomes according to each method. Methods Population-based retrospective cohort of all patients with Non-Valvular Atrial Fibrillation, who were newly prescribed acenocoumarol, apixaban, dabigatran or rivaroxaban from Nov2011 to Dec2015 in the Valencia region (Spain). Patients were followed for 12 months to assess adherence using three different approaches (PD, D1 and D2 cohorts). To analyze the relationship between adherence (PDC≥80) assessed by different approaches and outcomes (death for any cause, stroke or bleeding) Cox regression models were used. For the identification of clinical events patients were followed from the end of the adherence assessment period to the end of the available follow-up period. Results PD cohort included all patients with an OAC prescription (n=38,802), D1 cohort excluded fully non-adherent patients (n=265) and D2 cohort also excluded patients without two refills separated by 180 days (n=2,614). PDC≥80% ranged from 94% in the PD cohort to 75% in the D1 cohort. Drug exposure among adherent (PDC≥80%) and non-adherent (PDC<80%) patients was different between cohorts. In adjusted analysis, high adherence reduced the risk of death (Hazard Ratio (HR): from 0.82 to 0.86) and (except in the PD cohort) the risk for ischemic stroke (HR: from 0.61 to 0.64) without increasing the risk of bleeding. Conclusion Common approaches to assess adherence using a measures based on days’ supply exclude non-adherent patients and, also, misattribute periods of doctors’ discontinuation to patient non-adherence, misestimating adherence overall. Additionally, when using the PDC80 threshold, very different groups of patients may be classified as adherent or non-adherent depending on the method used for the calculation of adherence measures. High adherence and high exposure to OAC in NVAF patients was associated with better outcomes.